2022
DOI: 10.17219/acem/121930
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of ACO3 protein in diabetic retinopathy through the PI3k/Akt signaling pathway

Abstract: Background. Diabetic retinopathy (DR) is one of the most common complications of diabetic microvascular disease and its pathogenesis is complicated. The PI3k/Akt signaling pathway plays an important role in the angiogenesis of DR. Objectives.To explore the molecular mechanisms of the ACO3 protein and related proteins in DR, in order to provide a scientific theoretical basis for the clinical treatment of this disease. Materials and methods.A DR rat model was used in this study. One group (anti-ACO3 group, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…PI3K/AKT signaling is a major pathway in insulin, and aberrant PI3K/AKT signaling is a common pathogenesis of diabetes [ 42 ]. Previous studies have demonstrated that PI3K/AKT signaling plays a critical role in the neovascularization of diabetic retinopathy, and upon activation, PI3K/AKT signaling may extend the survival period of endothelial cells and synergize with VEGF to jointly mediate cell survival and migration, which finally triggers neovascularization [ 43 , 44 ]. In addition, PI3K signaling may be activated by hypoglycemia and hypoxia under a diabetic condition, and activation of AKT may induce vascular dilation, remodeling, and vascularization [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT signaling is a major pathway in insulin, and aberrant PI3K/AKT signaling is a common pathogenesis of diabetes [ 42 ]. Previous studies have demonstrated that PI3K/AKT signaling plays a critical role in the neovascularization of diabetic retinopathy, and upon activation, PI3K/AKT signaling may extend the survival period of endothelial cells and synergize with VEGF to jointly mediate cell survival and migration, which finally triggers neovascularization [ 43 , 44 ]. In addition, PI3K signaling may be activated by hypoglycemia and hypoxia under a diabetic condition, and activation of AKT may induce vascular dilation, remodeling, and vascularization [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/ AKT signaling is a major pathway in insulin, and aberrant PI3K/AKT signaling is a common pathogenesis of diabetes [42]. Previous studies have demonstrated that PI3K/AKT [43,44]. In addition, PI3K signaling may be activated by hypoglycemia and hypoxia under a diabetic condition, and activation of AKT may induce vascular dilation, remodeling, and vascularization [45].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT signaling plays a key role in neovascularization in DR. Activation of PI3K/AKT signaling by AGEs combined with RAGE may prolong endothelial cell survival, and cooperate with VEGF to promote retinal endothelial cell proliferation and migration, ultimately promoting neovascularization [ 30 , 31 ]. Activated AKT can mediate a variety of downstream target proteins, such as cell growth and proliferation through phosphorylation of mTOR, and apoptosis through inhibition of adverse expression [ 32 , 33 ].…”
Section: Rage Is Involved In Promoting Neovascularizationmentioning
confidence: 99%